JOHAN GALTUNG'S CONCEPT OF PEACE CULTURE AND ITS IMPLEMENTATION IN INDONESIA - Aloysius Jondar; Agus Purbo Widodo; Johan de Fretes; Lukman Hakim; Susanto Susanto; Muhammad Sujud (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2022)
This research focuses on Johan Galtung’s theory of the culture of peace. Based on his thoughts, the problems in this study are: 1). What is Johan Galtung's concept of a culture of peace? 2). The methods and approaches used by Johan Galtung in dealing with conflicts so as to get a culture of peace? 3). Where is the relevance of Johan Galtung's thoughts to the cultural conditions of peace in Indonesia? His findings, Johan Galtung 's thoughts on a culture of peace without war and physical violence as a focus on preventing violent conflicts and wars between and within countries. Johan Galtung added the need for the abolition of construction to the need to eliminate physical violence and war. Indonesia's active participation in world peace is also realized in the positive reality of peace, namely the realization of a sense of security and economic justice from the existing system to eliminate racial, ethnic and religious discrimination based on social. This is supported by the philosophical existence of a culture of peace in several regions in Indonesia, namely 1). Pela Gandong in Maluku as an alliance system between villages based on a pledge of blood friendship, 2). In Javanese society, the term, namely tepa selira, shows us not to do something to other people, nor do we want to be treated like that, 3). In the Fak-Fak community, it is known as the motto of one three stone stove, 4). philosophic culture of Hambor in Manggarai through traditional rituals, 5). Chinese cultural philosophy, namely Ping. To prevent conflict in Indonesia, it is necessary to provide training and education in a culture of peace through schools and campuses in order to support the business climate in this country.